2019
DOI: 10.7150/ijbs.30168
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of STAT3 Phosphorylation Promotes Apoptosis and Chemosensitivity in Human Osteosarcoma Induced by Raddeanin A

Abstract: Osteosarcoma (OS) is the most common primary bone malignancy in adolescents. One major obstacle for current OS treatment is drug-resistance. Raddeanin A (RA), an oleanane-type triterpenoid saponin, exerts anti-tumor effects in several tumor models, but the effect of RA in human drug-resistant OS remained to be elucidated. In the present study, we investigated the anti-tumor effects of RA in both drug-sensitive and drug-resistant OS cells and its underlying mechanism. RA inhibited cell proliferation and colony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…[15][16][17][18][19] Further research has demonstrated that the attenuation of STAT3 phosphorylation promotes apoptosis and chemosensitivity in MG-63, U2OS and HOS cells. 20 However, the precise role of the IL-6/STAT3 pathway in modulating the stemness properties of osteosarcoma has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Further research has demonstrated that the attenuation of STAT3 phosphorylation promotes apoptosis and chemosensitivity in MG-63, U2OS and HOS cells. 20 However, the precise role of the IL-6/STAT3 pathway in modulating the stemness properties of osteosarcoma has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ye et al found that NVP‐TAE684, a kinase inhibitor, could inhibit MDR1 function and reverse MDR1-mediated chemoresistance in osteosarcoma 13 . Using the same doxorubicin-resistant cell lines, Wang and colleagues demonstrated that the transcription factor STAT3 (signal transducer and activator of transcription 3) could activate MDR1 expression and that attenuation of STAT3 phosphorylation induced apoptosis and increased chemosensitivity 14 .…”
Section: Introductionmentioning
confidence: 99%
“…P-gp, also known as multidrug resistance protein 1 (MDR1), which is encoded by ATP-binding cassette subfamily B member 1(ABCB1), contributes to chemoresistance in various kinds of cancer (21). Wang et al (22)demonstrated that Raddeanin A restored doxorubicin chemosensitivity in OS drug-resistant U2OSR and KHOSR cells by downregulating MDR1. To further identify whether MDR1/p-gp is involved in CXCR4-mediated doxorubicin resistance, western blotting was utilized to detect the changes of p-gp expression after CXCR4 regulation.…”
Section: Discussionmentioning
confidence: 99%